Transparency and Public Participation: A Report Card on WTO Transparency Mechanisms - Marceau, Gabrielle; Hurley, Mikella (NLUJ, 2012)
In contemporary society where transparency has become a widely shared and recognized value, international organizations are increasingly being called upon to open their internal decision-making processes to greater public participation and scrutiny. The World Trade Organization [WTO], and its predecessor, the GATT, like many other institutions in the field of international economic law, have commonly been perceived as lacking sufficient transparency. However, since its inception in 1994, the WTO has systematically worked to increase public access to information, both in the context of rulemaking and dispute settlement, and has set an early example for other institutions. This article reviews the WTO’s efforts in this area, including recent developments on issues such as open hearings and amicus curiae briefs. Comparisons are drawn with other fora, particularly regional trade agreements and investor-State dispute settlement mechanisms. This transparency “report card” finds that, on the whole, the WTO’s track record compares favourably with that of other similar institutions. Nonetheless, some suggest that further work is warranted, particularly in the context of dispute settlement. The article concludes recalling practical suggestions that could help make the WTO even more transparent, and further increase the public’s trust in its mission.